Toxicity profile of thal-dex regime in patients with multiple myeloma - R., Dawnji S.; R., Reeja; M. R., Rakesh Praveen Raj (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study the spectrum, incidence and severity of toxicity among Multiple Myeloma patients receiving Thal-Dex in South Indian population. Methods: Between November 2005 and November 2005, 25 adult patients with previously- untreated Multiple Myeloma were assigned to receive Thal-Dex at Regional Cancer Centre, Trivandrum. During chemotherapy, patients were followed-up to detect the development of any toxicity symptoms. The toxicities recorded, were graded according to the criteria of the World Health Organization toxicity-guidelines. Results: In the 25 patients who received Thal-Dex, peripheral neuropathy, infection and constipation were significantly seen, while gastrointestinal toxicities were seen to a lesser extent, and haematological toxicities were low. Conclusions: The Thal-Dex regimen was tolerated well by majority of the patients and showed favourable toxicity profile, reiterating its acceptability as a front line antimyeloma regimen